Induction of liver-resident memory T cells and protection at liver-stage malaria by mRNA-containing lipid nanoparticles - Nakamae, Sayuri; Miyagawa, Satoshi; Ogawa, Koki; Kamiya, Mariko; Taniguchi, Mayumi; Ono, Akari; Kawaguchi, Maho; Teklemichael, Awet Alem; Jian, Jiun-Yu; Araki, Tamasa; Katagami, Yukimi; Mukai, Hidefumi; et al. (Frontiers in Immunology, 2023)
Recent studies have suggested that CD8 + liver-resident memory T (TRM) cells are crucial in the protection against liver-stage malaria. We used liver-directed mRNA-containing lipid nanoparticles (mRNA-LNPs) to induce liver TRM cells in a murine model. Single-dose intravenous injections of ovalbumin mRNA-LNPs effectively induced antigen-specific cytotoxic T lymphocytes in a dosedependent manner in the liver on day 7. TRM cells (CD8 + CD44 hi CD62L lo CD69 + KLRG1 -) were induced 5 weeks after immunization. To examine the protective efficacy, mice were intramuscularly immunized with two doses of circumsporozoite protein mRNA-LNPs at 3-week intervals and mRNA-LNPs and CD8 + T cells 2 This is a provisional file, not the final typeset article challenged with sporozoites of Plasmodium berghei ANKA. Sterile immunity was observed in some of the mice, and the other mice showed a delay in blood-stage development when compared with the control mice. mRNA-LNPs therefore induce memory CD8 + T cells that can protect against sporozoites during liver-stage malaria and may provide a basis for vaccines against the disease.